1988
DOI: 10.1001/jama.1988.03720010033036
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Human Immunodeficiency Virus Transmission From Heterosexual Adults With Transfusion-Associated Infections

Abstract: The risk of human immunodeficiency virus (HIV) transmission was studied by interviewing and testing the serum of heterosexual contacts and casual family contacts of adults with transfusion-associated HIV infections. Two (8%) of 25 husbands and ten (18%) of 55 wives who had had sexual contact with infected spouses were seropositive for HIV. Compared with seronegative wives, the seropositive wives were older (median ages, 54 and 62 years; P = .08) and actually reported somewhat fewer sexual contacts with their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(67 citation statements)
references
References 39 publications
0
66
0
1
Order By: Relevance
“…five publications 14,16,83-85 were based on the US-CDC study 25 ) and estimates from the most recent or largest sample were included. Roth and Allen reported on two samples of the same study population that we assumed independent 59,60 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…five publications 14,16,83-85 were based on the US-CDC study 25 ) and estimates from the most recent or largest sample were included. Roth and Allen reported on two samples of the same study population that we assumed independent 59,60 .…”
Section: Resultsmentioning
confidence: 99%
“…The index case and time of infection are determined based on exposure to a salient risk factor 15-16,43,87,92 . However, in transfusion studies, the infection time of index cases can be determined more precisely from the date of the transfusion 16,25, 27,43,77,81-82 . Otherwise, it is estimated by exploring possible dates of infection or by defining a distribution of possible infection times using information from questionnaires and local epidemic curves or CD4+ cell counts 15-16,45,83-84,87,92 .…”
Section: Resultsmentioning
confidence: 99%
“…This simplifying assumption meant that, when a partnership between a susceptible and an infected individual was formed, infection was either transmitted or it wasn鈥檛 and this depended on the transmission probability per sexual partnership. An empirical justification for this was provided by the observed high transmission probability per sexual act in the case of gonorrhoea21 and the lack of a relationship within partnerships between the number of unprotected sex acts and the transmission of HIV 22 23. Such models inevitably showed that reducing rates of partner acquisition would reduce the incidence of STIs, but could not represent the use of condoms since the number of unprotected sex acts with a partnership was not included.…”
mentioning
confidence: 99%
“…However, previous work suggests that the number of sex acts which take place within a partnership is not an important determinant of transmission. 26 We have not modelled possible variability in the transmission probability of HIV from an infected individual during the course of the infection either as a result of antiviral therapy or natural history. Neither have we modelled the eVects of possible heterogeneity in either host susceptibility to infections or in pathogen strain infectivity.…”
Section: Discussionmentioning
confidence: 99%